Evaluation of a Commercial Direct Fluorescent-Antibody Assay for Human Metapneumovirus in Respiratory Specimens - Vinh, Donald C. (American Society for Microbiology (ASM), 2008)
The performance of a commercially manufactured direct fluorescent-antibody assay kit for human metapneumovirus was compared to that of reverse transcriptase PCR, the current “gold standard.” The kit demonstrated a sensitivity of 95.2%, a specificity of 100%, and an accuracy of 98.9%.